Further understanding of epigenetic dysfunction of the retinal pigment epithelium in AMD. (3rd July 2020) - Nashine, Sonali; Kenney, Maria Cristina
ABSTRACT: Introduction: Modulation of epigenetic mechanisms that contribute to retinal development may render the eye susceptible to age-related macular degeneration (AMD). Progression of AMD involves alterations of epigenome such as CpG methylation and histone modifications, and study of the epigenetic regulation of molecular/cellular pathways associated with AMD might identify target epigenetic markers for treatment of AMD. Areas covered: In this review, we provide an overview of the influence of epigenetic factors on signaling pathways/related genes associated with AMD, mainly hypoxia, angiogenesis, inflammation, complement, and oxidative stress; and discuss the critical role of microRNAs in AMD. Expert opinion: Better understanding of epigenetic-mediated and microRNA-mediated regulation of the AMD disease-related pathways would help to assess the risk of developing AMD besides providing valuable insight on potential target candidates for AMD therapy.